2011
DOI: 10.1097/jto.0b013e31821671b6
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Lung Cancer Staging with Positron Emission Tomography in the Cancer Care Outcomes Research and Surveillance (CanCORS) Study

Abstract: Introduction Disparities in treatment exist for non-white and Hispanic patients with non-small-cell lung cancer, but little is known about disparities in the use of staging tests or their underlying causes. Methods Prospective, observational cohort study of 3638 patients with newly diagnosed non-small-cell lung cancer from 4 large, geographically-defined regions, 5 integrated health care systems and 13 VA health care facilities. Results Median age was 69 years, 62% were men, 26% were Hispanic or non-white,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Our results, demonstrating lower use of PET among black beneficiaries compared with white beneficiaries, are consistent with these prior reports of racial disparities in the use of new technologies and, of note, also with the study of PET use in nonā€“small-cell lung cancer in the Cancer Care Outcomes and Research Surveillance population [8]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results, demonstrating lower use of PET among black beneficiaries compared with white beneficiaries, are consistent with these prior reports of racial disparities in the use of new technologies and, of note, also with the study of PET use in nonā€“small-cell lung cancer in the Cancer Care Outcomes and Research Surveillance population [8]. …”
Section: Discussionsupporting
confidence: 92%
“…The importance of sociodemographic factors in PET use is important to examine given well-documented sociodemographic disparities in use of new technologies in general and, more specifically, on the basis of a recent study of PET use in patients with nonā€“small-cell lung cancer. That study, using the Cancer Care Outcomes and Research Surveillance study population, found 13% lower use of PET among nonwhites and Hispanics compared to non-Hispanic whites after adjusting for income, education, insurance, and health care setting [8]. A national examination of sociodemographic patterns of PET use is compelling, particularly for cancers for which PET is covered by Medicare because that population accounts for the majority of cancers in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the more affluent and educated are more likely to have a diagnostic confirmation of cancer, substantiating that socioeconomic factors do impact on the diagnostic workup. This is in keeping with multiple studies highlighting differences in cancer staging procedures between different racial/socioeconomic groups (Merrill et al , 2000; Gould et al , 2011) and among the elderly (Wedding and Lichtman, 2013). …”
Section: Discussionsupporting
confidence: 88%
“…A previous analysis of PET (26) examined patients with NSCLC in the Cancer Care Outcomes Research and Surveillance Consortium (CanCORS) during the later phase of PET adoption between 2003 and 2005 and found a similar 10% differential use of PET according to race and education level. Our study examined regional measures of education, race, and income, whereas the CanCORS analysis used individuallevel metrics.…”
Section: Health Policy and Practice: Variations In Pet Use In Medicarmentioning
confidence: 89%